Long-period changes of the air temperature in Tatarstan and their forecast till the end of the 21st century - Perevedentsev, Yuri P.; Shantalinskii, Konstantin M.; Sherstukov, Boris G.; Nikolaev, Alexander A. (Journal of the Belarusian State University. Geography and Geology, 2019)
Long-term changes in air temperature on the territory of the Republic of Tatarstan in the 20th–21st centuries are considered. The periods of unambiguous changes in the surface air temperature are determined. It is established that the average winter temperature from the 1970s to 2017, increased in the Kazan region by more than 3 °C and the average summer temperature increased by about 2 °C over the same period. The contribution of global scale processes to the variability of the temperature of the Kazan region is shown: it was 37 % in winter, 23 % in summer. The correlation analysis of the anomalies of average annual air temperature in Kazan and the series of air temperature anomalies in each node over the continents, as well as the ocean surface temperature in each coordinate node on Earth for 1880 –2017, was performed. Long-distance communications were detected in the temperature field between Kazan and remote regions of the Earth. It is noted that long-period climate fluctuations in Kazan occur synchronously with fluctuations in the high latitudes of Asia and North America, with fluctuations in ocean surface temperature in the Arctic ocean, with fluctuations in air temperature in the Far East, and with fluctuations in ocean surface temperature in the Southern hemisphere in the Indian and Pacific oceans, as well as air temperature in southern Australia. It is suggested that there is a global mechanism that regulates long-term climate fluctuations throughout the Earth in the considered interval of 200 years of observations. According to the CMIP5 project, climatic scenarios were built for Kazan until the end of the 21st century.
Keywords: air temperature; climate change; linear trend; climate models; climatic scenarios